Edukasi Patuhi Protokol Kesehatan pada UMKM dan Masyarakat di Banjar Taman Sari - Suidarma, I Made; Gayatri, Ni Nyoman Putri; Proyoga, Setiawan Hadi (Jurnal PKM: Pengabdian Kepada Masyarakat, 2024)
The emergence of the Covid-19 pandemic has spread in almost all parts of the world, bringing adjustments to the order of life in all fields, not only in the health sector, but also in the economic and social fields, including the education delivery system. Infection with Covid-19 causes high mortality in various countries, but until now MSMEs and the public are still not aware of the dangers of the Covid-19 pandemic. This is due to several conditions such as low knowledge about Covid-19 and suboptimal education in implementing health protocols. Therefore, this service aims to provide education and understanding about Covid-19 and how to implement health protocols to MSMEs and the community in Banjar Taman Sari, Sanur Village. In addition, providing recommendations that can help improve compliance with health protocols at the MSME level and the community as a whole. The methods of activities used are: 1) Observation, carried out to observe directly or indirectly the condition of the community and MSMEs in the Banjar Taman Sari area, Sanur Village in implementing health protocols; 2) Implementation of Activities, by creating eflyers that will be distributed online to the public, as well as distributing posters to each MSME; 3) Education, at this stage carry out the delivery of education in the Banjar Taman Sari area. After the implementation of educational activities to MSMEs and the community, MSMEs and people in Banjar Taman Sari understand the dangers of Covid-19 and the importance of implementing health protocols, so that it can contribute to helping the government reduce the increase in Covid-19 patients.